(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzed the main threats to economic security in the banking sector. The concept of economic security of the banking system is defined and its content is disclosed. The key directions and tasks of ensuring the stability of banks in modern conditions are considered. The practical significance of the study lies in the possibility of using the results obtained to develop measures to strengthen economic security and improve the efficiency of the banking sector.